Karakteristik Hidrogeokimia Akuifer Tak Terkekang Kawasan Pesisir Pulau Weh, Aceh - Wisnu Arya Gemilang, Nia Naelul Hasanah Ridwan, Ulung Jantama Wisha (Jurnal Sumber Daya Air)
Marine tourism development in the Weh Island, Aceh Province needs several supports to enhance the amount of tourism visits such as groundwater availability. Groundwater quality evaluation in the unconfined aquifer systems is essential to assess the ground water advisability. One of the evaluation methods to observe the quality and characteristics of groundwater is physical and chemical parameters measurements completed by geological conditions and groundwater hydrogeochemical characteristics. Ground water facies is divided into five types including CaHCO3, CaCl, NaCl, NaHCO3, and the solution of CaMgCl. Rock weathering is the main factor to determine facies type of groundwater in Weh Island. As much as 54.55% of ground water samples are influenced by the seawater according to Na/Cl ratio. Based on the distance from coastline to Na and Cl elements, it shows a correlation by which the closer toward coastal, the higher salinity level of groundwater. Nevertheless, the entire samples occupy the requirement for daily consumption and utilization according to standardization by WHO, 1993 and Ministry of Health No: 492/MENKES/PER/IV/2010. Therefore, the fresh water provision that is feasible to support marine tourism development in Weh Island can be provided, despite the interpretation result of groundwater chemical data, seawater influence on groundwater takes place.